2017
DOI: 10.1186/s12889-017-4096-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health status of women who have regular sexual relations with men who have sex with men in mainland China

Abstract: BackgroundMen who have sex with men (MSM) are a high-risk group for sexually transmitted diseases (STDs) and human immunodeficiency virus (HIV) infection. In China, the vast majority of MSM feel forced to marry or plan to marry women, according to traditional Chinese culture. Women who have regular sexual relations with MSM, called tongqi in mainland China, live with a high risk of STDs or HIV infection, but these risks are often ignored. Our investigation of this group of the women is a preliminary study that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…From the database and handsearching 627 articles were initially identified and 11 studies (Tang and Zhang, 2013;Liu and Tang, 2014a;Tang and Liu, 2014;Tang and Yu, 2014;Zhang et al, 2014Zhang et al, , 2015Li X. H. et al, 2016;Li et al, 2017;Wu et al, 2018;Yan et al, 2019) met the selection criteria and were selected for the review (see Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the database and handsearching 627 articles were initially identified and 11 studies (Tang and Zhang, 2013;Liu and Tang, 2014a;Tang and Liu, 2014;Tang and Yu, 2014;Zhang et al, 2014Zhang et al, , 2015Li X. H. et al, 2016;Li et al, 2017;Wu et al, 2018;Yan et al, 2019) met the selection criteria and were selected for the review (see Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Tongqi in China are a high-risk population of HIV and sexual transmitted diseases. For instance, Li et al (2017) reported that in a sample of 144 Chinese gay wives, less than 30% had undergone HIV screening and 5.6% were HIV-positive; furthermore 35.3% had sexually transmitted infections (STIs). The literature was inconsistent with reporting wives' use of condoms during sexual intercourse with their husband.…”
Section: Sexual Health Issuesmentioning
confidence: 99%
See 3 more Smart Citations